2001
DOI: 10.1016/s0893-133x(00)00169-x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Enhances Expression of Adenosine A1 Receptor mRNA and Signaling in Cultured Rat Cortical Astrocytes and Brain Slices

Abstract: The inhibitory neuromodulator adenosine is released in the brain in high concentrations under conditions of exaggerated neuronal activity such as ischemia and seizures, or electroconvulsive treatment. By inhibiting neural overactivity, adenosine counteracts seizure activity and promotes neuronal survival. Since stimulation of adenosineAdenosine, as a metabolite of ATP, nature's general energy source, has acquired early in evolution the general function of signaling and counteracting a dysbalance of energy supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
3

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 64 publications
1
37
0
3
Order By: Relevance
“…We previously showed that IL-6 induces the expression of adenosine A 1 receptors in glia cells (Biber et al, 2001), where even modest changes in A 1 receptor expression cause marked changes in adenosine A 1 receptor-meditated signaling (Biber et al, 1997). Now, we extended these findings to neurons, the brain cells where the predominant expression of adenosine A 1 receptors occurs (Onodera and Kogure, 1988;Ulas et al, 1993;Swanson et al, 1995) and where adenosine acts to refrain excitatory transmission and to protect from uncoordinated firing (Dragunow, 1988;Dunwiddie and Masino, 2001).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…We previously showed that IL-6 induces the expression of adenosine A 1 receptors in glia cells (Biber et al, 2001), where even modest changes in A 1 receptor expression cause marked changes in adenosine A 1 receptor-meditated signaling (Biber et al, 1997). Now, we extended these findings to neurons, the brain cells where the predominant expression of adenosine A 1 receptors occurs (Onodera and Kogure, 1988;Ulas et al, 1993;Swanson et al, 1995) and where adenosine acts to refrain excitatory transmission and to protect from uncoordinated firing (Dragunow, 1988;Dunwiddie and Masino, 2001).…”
Section: Discussionmentioning
confidence: 60%
“…Tissue was lysed in guanidinium isothiocyanate/mercaptoethanol buffer and total RNA was extracted with one phenol/chloroform step (Chomczynski and Sacchi, 1987) and transcribed into cDNA as described (Biber et al, 2001). …”
Section: Rna Isolation and Reverse Transcription-polymerase Chain Reamentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been supported by the demonstration of an epilepsy-induced decrease in A 1 receptor expression in chronic seizures [67,[158][159][160]228] and adaptive changes in Ado receptors after seizures [111]. Activation of A 2B receptors by elevated Ado levels may induce the release of proinflammatory interleukin-6 (IL-6) from astrocytes leading to increased expression of A 1 receptors and their functions in the brain [229,230], which may explain (i) the increase of A 1 receptor expression after seizures parallel with increasing Ado level and (ii) the higher level of IL-6 in the brain areas (e.g., in the hippocampus and cortex) of epileptic patients and rats [186,[231][232][233], which may have a protective effect against subsequent seizures [230]. In addition, an increase in A 1 receptor density has been demonstrated in the epileptic tissue, for example, in PTZ kindling mice and kainic-acid-treated rats, which may also be an adaptive/protective mechanism against hyperexcitability-induced seizures and convulsions [96,230,[234][235][236][237][238][239].…”
Section: Adenosine Receptor Agonists and Antagonistsmentioning
confidence: 96%
“…Concurrently, IL-6 can decrease IL-1 and TNF-α synthesis in activated monocytes and may increase the production of IL-1Ra and soluble TNF receptors to decrease the inluence of these largely pro-inlammatory cytokines [204,205]. IL-6's neuroprotective efects have been shown to be mediated via the upregulation of adenosine A1 receptors on cells [206]. IL-6 also potentially aids in tissue remodeling and recovery through the initiation of astrogliosis and angiogenesis after injury [202,207,208].…”
Section: Mixed Inlammatory and Anti-inlammatory Cytokine Interleukin-6mentioning
confidence: 99%